ELECTRONICS HUMAN RESOURCE MANAGEMENT IN SOCIETY 5.0 - Aini, Badrul; Kariwardati, Kariwardati; Mardalia, Mardalia; Khuzaini, Khuzaini; Shaddiq, Syahrial (Journal Competency of Business, 2023)
This research aimed to analyze the implementation of Electronic Human Resource Management (EHRM) in Indonesia. The approach used in this research was descriptive qualitative research which aims to provide an overview of the focus of this research. The results of the first study were the implementation of EHRM in Indonesia and motivated by management's awareness of the era of technological development, where control was fully aware that utilizing Information and Communication Technology (ICT) developments in Indonesian territory. Then it can create a better organizational future, as well as improve the quality of work and service. Secondly, in preparing for the implementation of EHRM, the management of all regions in Indonesia took several steps, namely; survey and analysis of work needs in each existing field, carrying out planning in society 5.0.